Substitusi Tepung Pucuk Indigofera zollingeriana dengan Bungkil Kedelai Terhadap Peforma Produksi Puyuh Petelur Pemeliharaan 8 Minggu - Fira Faradillah (Jurnal Peternakan (Jurnal of Animal Science), 2018)
The study used 200 Japanese quail (Cortunix Cortunix japonica) aged eight weeks with a daily egg production of > 50%. This research aimed to study the substitutions of soybean meal (SBM) with Indigofera zollingeriana top leaf meal (ILM) in the diet on of the quail production performance. The experiment was conducted using a complete random design with five treatments and four repeats (10 quail tails each). The dietary treatment contained fve kind of combination of of SBM and ILM, R0= diets contained 18% SBM without ILM, R1= 16.2% SBM and 2.66% ILM, R2= 14.4% SBM and 5.32% ILM, R3= 12.6% SBM and 7.98% ILM, R4= 9% SBM and 13.3% ILM. The result showed that the used 2.66%, 5.32%, 13.3% ILM (R4) significantly (P<0.05) to quail egg production, egg mass production, and ration conversion. The conclusion of this sstudy was Indigofera zollingeriana top leaf meal could be used as much as 13.3% in the diets and could improve the quail production performance.Key words : Indigofera zollingeriana, Production performance Quail,